Comparison of Changes in Cortisol Levels in the Blood of Patients Undergoing Craniotomy Using Continuous Infusion Lidocaine and Fentanyl - Syaputra, Adhika; Irina, Rr Sinta; Lubis, Andriamuri Primaputra; Harahap, Juliandi (https://snacc.org/wp-content/uploads/2019/fall/Intl-news3.html, 2024)
Background and Objectives: Craniotomy is a surgical procedure that involves part of the skull, temporarily removing it to expose the brain and carrying out intracranial procedures. The surgery can be considered as the standard model for assessing cortisol as a stress response. Cortisol in the blood can cause hemodynamic and physiological changes in the body such as increased heart rate, increased blood pressure, and also increased blood sugar levels. Some literature showed that continuous infusion of fentanyl and lidocaine - has an effect in maintaining the responses to stress, namely the level of cortisol in the blood. The aim aimed to determine the comparison of changes in cortisol levels in the bloodpatients undergoing craniotomy using continuous infusion lidocaine and continuous infusion fentanyl.Subject and Method: This research used a double-blind randomized controlled trial (RCT) with a pre-test and post-test with a control group design. This study divided the samples into 2 groups. Continuous infusion of lidocaine and continuous infusion of fentanyl were then checked for cortisol levels in the patient's blood before and after undergoing craniotomy.Results: The result of 28 samples that underwent craniotomy, 6 samples were excluded, so the total number of samples analyzed was 22 samples. Differences in mean cortisol levels before and after surgery in the lidocaine and fentanyl groups were 193.90 nmol/L and 153.90 nmol/L respectively with a P value of 0.021.Conclusion: In the study, it was found that cortisol levels increased in both fentanyl and lidocaine groups after a craniotomy. There is a significant difference between the two groups of fentanyl and lidocaine, where statistically the fentanyl group was better at maintaining blood cortisol levels after craniotomy than the lidocaine group.